2022
DOI: 10.3390/microorganisms10081569
|View full text |Cite
|
Sign up to set email alerts
|

ITS rDNA Barcodes Clarify Molecular Diversity of Aquatic Hyphomycetes

Abstract: Aquatic hyphomycetes are key microbial decomposers of allochthonous organic matter in freshwater ecosystems. Although their importance in carbon flow and food webs in streams is widely recognized, there are still gaps in our understanding of their molecular diversity and distribution patterns. Our study utilized the growing database of ITS rDNA barcodes of aquatic hyphomycetes (1252 sequences) and aimed to (i) produce new barcodes for some lesser-known taxa; (ii) clarify the taxonomic placement of some taxa at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In our study, a proportion of more than one-third of the cells showed sigmoid morphologies. Hence, using a molecular barcode for the identification of less represented taxa among sigmoid cells, as performed in our workflow, has the potential to significantly improve our understanding of aquatic fungal diversity [Bärlocher 2010;Nilsson et al 2019], taking into account that aquatic hyphomycetes and other aquatic fungi are taxonomically highly divergent [Franco-Duarte et al 2022][Grossart et al 2019. As the ITS region as single marker may not be robust enough to cover this diversity [Kauserud 2023], an extension to the neighboring SSU and LSU regions holds to benefit of a more robust phylogenetic placement, and its reusability in future environmental amplicon studies, which usually depend on either one of these three ribosomal regions.…”
Section: Accurate Classification Of Aquatic Hyphomycetes Conidiamentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, a proportion of more than one-third of the cells showed sigmoid morphologies. Hence, using a molecular barcode for the identification of less represented taxa among sigmoid cells, as performed in our workflow, has the potential to significantly improve our understanding of aquatic fungal diversity [Bärlocher 2010;Nilsson et al 2019], taking into account that aquatic hyphomycetes and other aquatic fungi are taxonomically highly divergent [Franco-Duarte et al 2022][Grossart et al 2019. As the ITS region as single marker may not be robust enough to cover this diversity [Kauserud 2023], an extension to the neighboring SSU and LSU regions holds to benefit of a more robust phylogenetic placement, and its reusability in future environmental amplicon studies, which usually depend on either one of these three ribosomal regions.…”
Section: Accurate Classification Of Aquatic Hyphomycetes Conidiamentioning
confidence: 99%
“…Tetracladium is represented by a well-defined clade (SI-Supplementary data: Figure S1), however no clear separation among the species of both genera is apparent [Baschien et al 2013;Franco-Duarte et al 2022]. Although having less data for the FRO, this pattern seems to persists when considering the ITS, SSU and LSU region, seperately (SI-Supplementary data: Figure S2-S4), or all three regions together (Figure 2).…”
Section: Accurate Classification Of Aquatic Hyphomycetes Conidiamentioning
confidence: 99%
See 1 more Smart Citation
“…After exploring fungal rRNA genes, Schoch et al in 2012 identified the ITS as the possible universal DNA barcode identifier for fungi [ 24 , 62 ] , although currently, it is still not clear which of the two ITS components has the better resolution in strain prediction. Recent findings has shown that both regions suffer from amplification biases, resulting in an uneven representation of synthetic fungal communities [ 63 - 65 ] : ITS1-based PCR appears to favor Basidiomycota, whereas Ascomycota seems to be favored by ITS2-based PCR [ 66 - 68 ] , although this consideration should not be generalized. In fact, there are known ascomycetes species (such as the ones belonging to the genera Saccharomyces and Komagataella ) that are discriminated with greater resolution by employing the ITS1 marker [ 69 ] .…”
Section: Characterising the Mycobiome: Identification And Technologic...mentioning
confidence: 99%
“…Only a few aero-aquatic fungi belong to Basidiomycota and Orbiliomycetes. On the other hand, the aquatic mitosporic fungi (Ingoldian fungi) were also found polyphyletic among Ascomycota and Basidiomycota, while their major lineages belong to Helotiales, Leotiomycetes, followed by Dothideomycetes, Sordariomycetes, Basidiomycota and Orbiliomycetes (Duarte et al, 2013;Franco-Duarte et al, 2022). Thus, it is presumed that the almost the same groups of Ascomycota and only the small number of species of Basidiomycota have evolved to adapt to freshwater habi-tats as aero-aquatic fungi or aquatic fungi by applying their own strategy for conidial dispersal and colonization on substrates.…”
Section: Phylogenymentioning
confidence: 99%